Macroinvertebrates as Bioindicators of Water Quality in Karang Beach, Bali - Putra, Gede Bayu Hendra Adi; Radithya, Rafi; Dewi, Putu Anggi Handaresta; Aprilia, Revalina; Pratama, Made Dendy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Karang Beach is a shallow water with a sandy substrate mixed with coral fragments and seagrass beds that support the life of benthic organisms. This study aims to determine the water quality at Karang Beach using macroinvertebrates as bioindicators. Sampling was conducted on November 1 and 25, 2025, using field survey methods (in situ) and laboratory analysis (ex situ). Water quality parameters measured included temperature, pH, turbidity, and current velocity. The measurement results showed relatively stable water conditions with an average temperature of 25.5°C, pH 8.1, and turbidity ranging from 3.3–4.8 NTU. The macroinvertebrates found came from the families Toxopneustidae, Grapsidae, and Holothuriidae. Analysis using the Family Biotic Index (FBI) at stations 1 to 4 showed that the water quality at Karang Beach was in a moderately stressed to poor condition, characterized by the dominance of organisms tolerant to environmental disturbances.